Redescription of Iberoiulus cavernicola Ceuca, 1967, and the relationships of the genus Iberoiulus Mauriès, 1985 (Diplopoda, Julida, Blaniulidae) - Enghoff, Henrik; Reboleira, Ana Sofia P. S. (Zootaxa, 2014)
The Iberian blaniulid millipede Iberoiulus cavernicola Ceuca, 1967, is redescribed based on abundant new material collected in a cave in Villaluenga del Rosario, Cádiz, Spain. The relationships of the genus Iberoiulus Mauriès, 1985, to other blaniulid genera are discussed.